Effect of biofertilizer and chemical fertilizer on growth and production of Panicum maximum - Ni Putu Suratmini; Supriyati .; I Heliati; I.P Kompiang (Jurnal Ilmu Ternak dan Veteriner, 2002)
A glass-house experiment was conducted to study the effect of biofertilizer, chemical fertilizer and their combinations on the growth and production of Panicum maximum. Four cultivars of Panicum maximum were used, namely cv. Riversdale, cv. Petrie, cv. Natsukaze and cv. Natsuyukata. The grasses were planted in Latosol soil. The treatments with 3 replicates were: (1) control, (2) urea 100 kg N/ha, (3) biofertilizer 10 l/ha and (4) urea 50 kg N/ha + biofertilizer 10 l/ha. The grass was harvested every 40 days for 10 times and data was polled. The average production of grass for cv. Riversdale was 20.0 pols, height was 77.2 cm, fresh weight was 40.5 g and dry weight was 9.0 g. The average production of grass for cv. Petrie was 36.4 pols, height was 63.9 cm, fresh weight was 42 g and dry weight was 9.2 g. The average production of grass for cv. Natsukaze was 28.6 pols, height was 67.2 cm, fresh weight was 40.7 g and dry weight was 9.2 g. The average production of grass for cv. Natsuyukata was 36.9 pols, height was 74.9 cm, fresh weight was 45.3 g and dry weight was 9.7 g. The average production of treatment (I) were 17.2 pols, height 59.7 cm, fresh 11.4 g and dry weight 2.6 g. The average production of treatment (2) were 22.8 pols, height 61.1 cm, fresh 19.3 g and dry weight 4.2 g. The average production of treatment (3) were 40.3 pols, height 82.5 cm, fresh 71.6 g and dry weight 14.9 g. The average production of treatment (4) were 41.4 pols, height 79.9 cm, fresh weight 66.1 g and dry weight 14.5 g. Biofertilizer significantly increased number of pols, height, fresh and dry weights grass production.   Key words: Biofertilizer, chemical fertilizer, production, Panicum maximum